Severe plexiform facial neurofibromatosis, type 1 with underdeveloped eyes and a novel NF1 mutation - Piranit Nik Kantaputra (2018)
A Thai woman, who was affected with neurofibromatosis type 1, was followed up and re-evaluated at ages 45, 61, and 67 years. Her mother and her three brothers were also affected. The proposita was very severely affected. She was born blind with underdeveloped eyeglobes and had large plexiform neurofibromas on her face. Her eyelids were gigantic and tears drained from the orifice between them. Cutaneous neurofibromas were observed all over her body. A novel mutation c.4821delA was identified in NF1 gene, which predicted truncation of neurofibromin (p.Leu1607fs). © 2012 Wiley Periodicals, Inc.